Length-Weight Relationship and Condition Factor of Amblypharyngodon mola (Hamilton-Buchanan, 1822) - PAL, MONALISA; MAHAPATRA, B. K.; MANDAL, B.; ROY, A. K. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
The Mola Carplet, Amblypharyngodon mola (Hamilton-Buchanan, 1822) is very popular fish in West Bengal due to its high nutritive status, rich in micro nutrients and its palatable taste. In West Bengal it is locally known as mourala or mola. The study of length-weight relationship of fishes provides a mathematical relationship between Length (L) and Weight (W) as a means of inter-conversion for estimating the weight from the known length and vice-versa. In the present study L-W relationship and condition factor of A. mola were estimated from 910 samples collected from different locality of South 24 Parganas during Feb. 2011 to Feb. 2014. The total length ranged from 20 to 87 mm and the total body weight ranged from 0.07 to 6.97g. The scatter diagram showed the linear relationship in between the Log length and Log weight of the fish. The relationship of length and weight was found positive and highly significant justifying a strong relationship between L-W of A. mola (r=0.97). The functional form of relationship between L-W of the species is fitted as Log W= -6.08 + 3.57 Log L. The equation is a very good fit as seen from the coefficient of determination value (R2 = 0.95). The ‘b’ value (b=3.57) is more than 3 indicating the positive allometric growth of the fish and found to be significantly different at 1% level. The fish does not follow the cube law strictly. The mean condition factor of the fish was found to 0.85 indicating extremely poor fish, thin body.